Study on International Chinese Language Communication in Indonesia Mainstream Media: 印尼主流媒体中的汉语国际传播研究 - Yu, Zhang; Tela, Irvan Aditya (Published by Confucius Institute UNS, 2024)
This paper investigates the representation of the Chinese language in three prominent Indonesian media outlets Kompas, Metro News, and Kumparan by analyzing reports from the period 2020-2023, with “Bahasa Mandarin” (Chinese language) as the primary keyword. The study employs a corpus-assisted discourse analysis methodology, incorporating the conceptual framework of semantic prosody to examine how the international dissemination of the Chinese language is portrayed in Indonesian media. By conducting a two-tier analysis, this research uncovers how the Chinese language is spreading in Indonesia through media discourse, with a particular focus on sentiment analysis based on statistical text analysis and media report corpora. Furthermore, this research sheds light on the broader dynamics of international Chinese language communication, offering insights into the role of the media in shaping public perceptions of the Chinese language. It also contributes to understanding the Chinese language's evolving position and dissemination strategies within Indonesia’s social and cultural landscape.